Using Administrative Data to Predict Suicide After Psychiatric Hospitalization in the Veterans Health Administration System - Kessler, Ronald C.; Bauer, Mark S.; Bishop, Todd M.; Demler, Olga V.; Dobscha, Steven K.; Gildea, Sarah M.; Goulet, Joseph L.; Karras, Elizabeth; Kreyenbuhl, Julie; Landes, Sara J.; Liu, Howard; Luedtke, Alex R.; et al. (Frontiers in Psychiatry, 2020)
There is a very high suicide rate in the year after psychiatric hospital discharge. Intensive post-discharge case management programs can address this problem but are not cost-effective for all patients. This issue can be addressed by developing a risk model to predict which inpatients might need such a program. We developed such a model for the 391,018 short-term psychiatric hospital admissions of US veterans in Veterans Health Administration (VHA) hospitals 2010-2013. Records were linked with the National Death Index to determine suicide within 12 months of hospital discharge (n=771). The Super Learner ensemble machine learning method was used to predict these suicides for time horizon between 1-week and 12-months after discharge in a 70% training sample. Accuracy was validated in the remaining 30% holdout sample. Predictors included VHA administrative variables and small area geocode data linked to patient home addresses. The models had AUC=.79-.82 for time horizons between 1-week and 6-months and AUC=.74 for 12-months. An analysis of operating characteristics showed that 22.4-32.2% of patients who died by suicide would have been reached if intensive case management was provided to the 5% of patients with highest predicted suicide risk. Positive predictive value (PPV) at this higher threshold ranged from 1.2% over 12 months to 3.8% per case manager year over 1 week. Focusing on the low end of the risk spectrum, the 40% of patients classified as having lowest risk account for 0-9.7% of suicides across time horizons. Variable importance analysis shows that 51.1% of model performance is due to psychopathological risk factors accounted, 26.2% to social determinants of health, 14.8% to prior history of suicidal behaviors, and 6.6% to physical disorders. The paper closes with a discussion of next steps in refining the model and prospects for developing a parallel precision treatment model.